"Effects of Petroleum Tax Design upon Exploration and Development" - Thomas R. Stauffer (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
The principle that conventional schemes for taxing petroleum or mineral resources are "inefficient" is illustrated using simulation calculations tested against an "ideal" system. Inefficiency is defined as the relative success in maximizing expected government revenues from the resources. Most systems fail because: 1) they leave oil in limbo, i.e. unproduced because of excessive fiscal burden; or 2) they unnecessarily increase the variance in the explorationist'c, rate of return by undertaxing large fields and overtaxing smaller but infra-marginal fields. This increases his discount rate and reduces taxable surplus. An "ideal" tax system is specified which maximizes government revenues while minimizing risk to the operator. Two criteria are developed: 1) the tax falls to zero on fields which yield only the minimum necessary rate of return ("marginal" fields); and 2) the after-tax present value of all fields is the same for all fields above a threshhold size. In particular, marginal fields, while contrib- uting little to expected values, do contribute to reducing variance and hence risk praemia by distributing the exploration costs over a higher probability of successful outcomes.